Exploring the Relationship Between Perceived Stress and Menstrual Health in Undergraduates Across Different Academic Disciplines - Tomar, Anamya; Deepshikha; Das, Sai Chandan; Juyal, Ruchi; Kaur, Gagndeep; Jain, Rajnish (Indian Journal of Community Health, 2025)
Background: Menstrual disorders are associated with high stress in females. The current study was carried out to assess the extent of perceived stress and its impact on the menstrual health among female students enrolled in various undergraduate courses, both medical and non-medical. Methods: A cross-sectional study was conducted, with the objective to find out the association of stress with menstruation health problems. Around 300 participants were selected, from MBBS, Nursing, and Paramedical/Engineering/Management. Two scales PSS-14 and GHQ-12 were used to detect emotional disturbances and level of stress. Results: The mean Perceived Stress Scale (PSS) score was 26.24 ± 6.411, with a minimum score of 11 and a maximum score of 47 among the study subjects. Maximum perceived stress was observed among nursing students, followed by students in other courses. The prevalence of Menstruation Disorders was recorded at 69.3% with the highest proportions observed among nurses. Among participants experiencing menstrual health problems, 31 (14.9%) reported no stress, while 177(85.1%) reported high stress levels. The results indicate a significant association between menstrual health problems and stress levels (?² = 4.405, p = 0.04). Conclusion: Early evaluation of stress among students will help reduce psychiatric morbidity and can also improve their academic performances.